Multifocal Motor Neuropathy - Nowacek, Dustin G.; Teener, James W. (Seminars in Neurology, 2012)
Multifocal motor neuropathy is an acquired disorder in which demyelination of motor axons, presumably due to autoimmune attack, results in progressive painless weakness without sensory loss. Motor axonal damage also occurs. It is a frequent mimic of motor neuron disease. Recognition of multifocal motor neuropathy is critical because it tends to be very responsive to treatment. Infusion of intravenous immunoglobulin is the initial treatment of choice, but other immunosuppressive treatments may also be effective. It appears that corticosteroids produce minimal benefit.
Keywords: multifocal motor neuropathy; chronic immune; mediated polyneuropathy; conduction block; intravenous immunoglobulin